GmWRKY16 Enhances Drought and Salt Tolerance Through an ABA-Mediated Pathway in Arabidopsis thaliana - Ma, Qibin; Xia, Zhenglin; Cai, Zhandong; Li, Lu; Cheng, Yanbo; Liu, Jia; Nian, Hai (Frontiers in Plant Science, 2019)
The WRKY transcription factors (TFs) are one of the largest families of TFs in plants that play multiple roles in plant development and stress response. In the present study, GmWRKY16 encoding a WRKY transcription factor in soybean was functionally characterized in Arabidopsis. GmWRKY16 is a nuclear protein that contains a highly conserved WRKY domain and a C2H2 zinc-finger structure, and has the characteristics of transcriptional activation ability, presenting a constitutive expression pattern with relative expression levels of over 4-fold in the old leaves, flowers, seeds and roots of soybean. The results of quantitative real time polymerase chain reaction (qRT-PCR) showed that GmWRKY16 could be induced by salt, alkali, ABA, drought and PEG-6000. As compared with the control, overexpression of GmWRKY16 in Arabidopsis increased the seed germination rate and root growth of seedlings in transgenic lines under higher concentrations of mannitol, NaCl and ABA. In the meantime, GmWRKY16 transgenic lines showed over 75% survival rate after rehydration, and enhanced Arabidopsis tolerance to higher salt and drought with higher proline and lower MDA accumulation, less water loss of the detached leaves, and accumulated more endogenous ABA than control under stress conditions. Further studies showed that AtWRKY8, KIN1 and RD29A were induced in GmWRKY16 transgenic plants under NaCl treatment. The expressions of ABA biosynthesis gene (NCED3), signaling genes (ABI1, ABI2, ABI4 and ABI5), responsive genes (RD29A, COR15A, COR15B, RD22) and stress-related marker genes (KIN1, LEA14, LEA76, CER3) were regulated in transgenic lines under drought stress. In summary, these results suggest that GmWRKY16 as a WRKY TF may promote the tolerance to drought and salt stresses through an ABA-mediated pathway.